Gene Mutations as Emerging Biomarkers and Therapeutic Targets for Relapsed Acute Myeloid Leukemia - Aziz, Habsah; Ping, Chow Y.; Alias, Hamidah; Ab Mutalib, Nurul-Syakima; Jamal, Rahman (Frontiers in Pharmacology, 2017)
It is believed that there are key differences in the genomic profile between adult and childhood acute myeloid leukemia (AML). Relapse is the significant contributor of mortality in patients with AML and remains as the leading cause of cancer death among children, posing great challenges in the treatment of AML. The knowledge about the genomic lesions in childhood AML is still premature as most genomic events defined in children were derived from adult cohorts. However, the emerging technologies of next generation sequencing have narrowed the gap of knowledge in the biology of AML by the detection of gene mutations for each sub-type which have led to the improvement in terms of prognostication as well as the use of targeted therapies. In this review, we describe the recent understanding of the genomic landscape including the prevalence of mutation, prognostic impact and targeted therapies that will provide an insight into the pathogenesis of AML relapse in both adult and childhood cases.